MANAJEMEN KINERJA SAMSAT PEKANBARU KOTA - Napitupulu, Yen Chintya; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Performance management of Samsat Pekanbaru City represent one of the process used to determine what have to reach and approach to manage and develop organization away of able to improve possibility that target will be able to reach certain within. But in reality of Samsat Pekanbaru City not yet earned perfectly in its execution to serve society, between expectation and fact conducted by discrimination is Samsat Pekanbaru City in giving of service.There are assumed procedure needn't specified by Samsat Pekanbaru City. Quality of officer of assumed Samsat Pekanbaru City still less in giving information to society concerning procedure they which must follow so that society motor vehicle can be processed by its administration. Accuracy of time at process penyelasaian of motor vehicle administration by Samsat Pekanbaru City which disagree with standard which have been specified.Theory concept the used is management theory according to Wibowo. This Indicators Research like input ( input), process, output ( output), and impact or benefit ( outcome). And added by factors influencing performance management that is found by factor writer of field that is certainty and clarity, generalization and justice, accuracy of officer quality and time.Factors influencing performance management that is found by factor writer of field that is certainty and clarity, generalization and justice, accuracy of officer quality and time. Jasa Raharja and also society accepting service in Samsat Pekanbaru Town. Intake by using Snowball tecnicaly. This Research represent research of deskriftif qualitative.Result of research, can be concluded that performance management given by Samsat Pekanbaru City in fact have walked better, but becoming constraint this time is to prepare of is source of management at phase process where in co-ordinating, cooperate and also communicate ought to Samsat Pekanbaru City use sixthly is source of the management to be able to yield performance which with quality to reach mission and vision of Samsat Pekanbaru City, and also to ensure that output than useful Samsat itself and affect at life of society. Other constraint that is done by specialized training inexistence is Samsat Pekanbaru Town to increase the quality of its officers in giving service to society, And also appreciation inexistence for officer which is haveachievement, so that officer do not motivat to conduct more attainment of done performance it.Keywords : PerformanceOf Management, Samsat Pekanbaru City